(untitled) (Computer systems and information technologies, 2024)
The paper presents a model for providing fault tolerance in the Internet of Things network, describes key concepts, entities and connections, and also defines the main stages and processes that are included in providing fault tolerance. This model is the basis of the functioning of the fault tolerance system. The concept of a fault tolerance system that integrates into existing Internet of Things networks is proposed. The concept of fault tolerance agents is introduced, which make up the basis of the fault tolerance system, and which communicate with each other to ensure the exchange of information about the occurrence of a fault. Two local fault tolerance mechanisms are proposed, which determine the functionality of the agents.